The effect of a chemically defined diet on the faecal flora and faecal steroid concentration. Issue 10 (October 1973) - Crowther, J. S.; Drasar, B. S.; Goddard, P.; Hill, M. J.; Johnson, K.
Abstract : The consumption of a chemically defined diet altered both the faecal flora and faecal steroids. Enterobacteria increased while enterococci and other lactic acid bacteria decreased in number. No other obvious change occurred. However, the alteration in the degree of degradation of the faecal neutral steroids may reflect some alteration in the anaerobic flora. Total excretion of both acid and neutral steroids was also reduced. On cessation of the diet both faecal flora and faecal steroids reverted to levels before the diet.